An interactive database of Leishmania species distribution in the Americas (2020)
The Americas have an elevated number of leishmaniasis cases (accounting for two-thirds of the worldwide disease burden) and circulating Leishmania species, and are therefore of interest in terms of epidemiological surveillance. Here, we present a systematic review of Leishmania parasite species circulating in the countries of the American continent, together with complementary information on epidemiology and geospatial distribution. A database was built from data published between 1980 and 2018 on Leishmania species identified in most of the American countries. A total of 1499 georeferenced points were extracted from published articles and subsequently located to 14 countries in the Americas. This database could be used as a reference when surveilling the occurrence of Leishmania species in the continent. © 2020, The Author(s).